The Effect of Using Smartphone Gadgets in the Digital Age on Interests and Thematic Learning Outcomes of SD N 173632 Porsea Students in the 2022/2023 Academic Year - Rati Ramalia Napitupulu; Nurmayani; Wildansyah Lubis; Lala Jelita; Faisal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find out how much influence the use of smartphone gadgets has on the thematic learning interests and outcomes of SD N 173632 Porsea students. The research method used is a quantitative method, with the type of ex-post facto research. The sample in this study was class V, which consisted of 34 students. Data collection techniques and research instruments used were questionnaires. Data analysis techniques used were normality test, linearity test, multicollinearity test, hypothesis testing with simple regression analysis and regression analysis of intervening variables. The results of the study show that there is a positive and significant influence on the use of smartphone gadgets on the interest and thematic learning outcomes of SD N 173632 Porsea students in the 2022/2023 academic year. Based on the results of a partial hypothesis test (t test) the t_count value was obtained for the variable smartphone gadget use for interest in learning, namely 3.680, which means t_count > t_table (3.680 > 2.037). Thus it can be concluded that there is a positive influence between the use of smartphone gadgets on the learning interests of SD N 173632 Porsea students in the 2022/2023 academic year. The t test for the variable interest in learning on learning outcomes obtained t_count is 2.627, which means t_count > t_table (2.627 > 2.037). Thus it can be concluded that there is a positive influence between the use of smartphone gadgets on the learning interest of SD N 173632 Porsea students in the 2022/2023 academic year.